Comparison of Growth Pattern in Neonates on Breast Feed Versus Formula Feed - Singh, Arun Kumar; Singh, Raj Kumar; Shah, Rajesh Prasad; Ahmad, Equbal; Ansari, Akhtar Alam; Islam, Mohammed Mansuri (Med Phoenix, 2017)
Background: Breast milk and colostrums are the first feeding sources for infant, providing nutrients, growth factors and immunological components. So we conducted this study to compare the growth pattern of neonates on breast feed versus formula feed. Methods: This study was done in the Department of Pediatrics, King Edward Medical University, Mayo Hospital, Lahore from 2015 July to 2016 July as cross sectional study. The Non Probability purposive sampling technique was used. Information on type of feeding was obtained from mothers. Subsequently neonates were divided in two groups on the basis of type of feeding (i.e. breast feeding or formula feeding). Results: In this study the mean age of the patients was 16.56±6.26 days and the mean gestational age of the patients was 8.52±0.97 months. The male to female ratio of the patients was 1.3:1. Statistically there was significant difference found between the weight gain in study groups at 10th, 14th week and 4th month follow up i.e. p-value<0.05. Conclusion: The prevalence of breastfeeding in infants in our study was 52.3%. Our results showed that the breast fed infants had better weight gain compared to formula fed infants; however there was no statistically significant difference in gain in length between breast fed and formula fed infants. Med Phoenix Vol.2(1) July 2017, 18-23